Essential personal finance : a practical guide for students - Luu, Liên, 1967-; Lowe, Jonquil; Butler, Jason (Financial planner) (Routledge, 2025)
Young people face unprecedented financial challenges: rising student debt, stiff competition for jobs, barriers to home ownership, dwindling state benefits and prospects of a longer working life. Essential Personal Finance is a guide to all the key areas of personal finance: budgeting, managing debt, savings and investments, insurance, securing a home and laying the foundations for retirement.It provides an introduction to some of the essential foundations of a modern undergraduate finance qualification, including: the nature of financial institutions, markets and economic policy that shape the opportunities and decisions individuals face the range of financial assets available to households, risk-return trade-off, basics of portfolio construction and impact of tax the importance of the efficient market hypothesis and modern portfolio theory in shaping investment strategies and the limitations of these approaches behavioural finance as a key to understanding factors influencing individual and market perceptions and actions using financial data to inform investment selection and create financial management tools that can aid decision-making The second edition has been fully updated and includes: more information on the cost of living crisis; Fintech, climate change, sustainable finance and cryptocurrencies; financial skills and calculations; tax, trust planning and wills; pensions; regulation and fraud; and additional case studies.Written by authors who contribute experience as financial advisers, practitioners and academics, Essential Personal Finance is a compelling combination of a textbook aimed at students on personal finance and financial services courses, and a practical guide for young people in building their own financial strength and capability.
Keywords: Finance, Personal.; elektronické knihy; electronic books